Individual design of the anterolateral thigh flap for functional reconstruction after hemiglossectomy: experience with 238 patients. Issue 6 (June 2016) - Wang, L.; Liu, K.; Shao, Z.; Shang, Z.-J.
Abstract: The aim of this study was to evaluate tongue function in patients with oral cancer treated surgically and reconstructed with anterolateral thigh free flaps (ALTFs). Patients ( N = 238) underwent primary reconstruction after hemiglossectomy between September 2012 and October 2014. Patients were divided into two groups according to the flap design: 'individual design' (ABC flap) and 'common design'. Patients were followed postoperatively and assessed after 6 months for the following functional outcomes: speech, deglutition, tongue mobility, and donor site morbidity. Intelligibility and deglutition were each scored by an independent investigator. Data were analyzed using SPSS version 16.0 software. No differences in mean speech intelligibility scores were observed between the two groups (good: P = 0.908; acceptable: P = 0.881). However, the ABC flap offered recovery advantages for swallowing capacity compared to the common design flap (MTF classification good: P = 0.028; acceptable: P = 0.001). The individualized ABC flap not only provides volume but also preserves mobility, speech intelligibility, and swallowing capacity. ALTFs require further improvement for the individualized functional reconstruction of the tongue after hemiglossectomy, but this work lays the foundation for these improvements.